2011
DOI: 10.1002/sia.3828
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, morphology and mechanical properties of Al2O3–Al graded coatings on China low activation martensitic steel substrates

Abstract: graded coatings were fabricated on China low activation martensitic steel and silicon substrates by RF magnetron sputtering. The coating composition and cross-section morphologies were investigated using X-ray photoelectron spectroscopy, Auger electron spectroscopy and field-emission scanning electron microscopy. The mechanical properties of the coatings were studied using nanoindentation, wafer-curvature measurements and microscratch tests. The results show that usable Al 2 O 3 -Al graded coatings could be fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The use of nanoindentation for the characterization of functional graded thin films is exploited for several applications such as protection against metal dusting [17], high speed cutting tools [18] or protection of martensic steel for reactors [19]. However, it was not possible to find any work concerning the nanomechanical characterization of functionally graded coatings for biomedical applications although many studies concerning the use of nanoindentation on the characterization of functionally graded biological materials such as bone [20,21] and dental enamel and dentin [22,23] have been published.…”
Section: Introductionmentioning
confidence: 99%
“…The use of nanoindentation for the characterization of functional graded thin films is exploited for several applications such as protection against metal dusting [17], high speed cutting tools [18] or protection of martensic steel for reactors [19]. However, it was not possible to find any work concerning the nanomechanical characterization of functionally graded coatings for biomedical applications although many studies concerning the use of nanoindentation on the characterization of functionally graded biological materials such as bone [20,21] and dental enamel and dentin [22,23] have been published.…”
Section: Introductionmentioning
confidence: 99%
“…The composite could overcome the conflict between the coating adhesion and mechanical strength. [ 8 ] The VC/Cr 3 C 2 /TiB 2 /TiC/Al 2 O 3 composite ceramic was prepared by a vacuum hot‐press sintering method, in which the gradient mechanic of Al 2 O 3 composite ceramic was obtained by adjusting content of VC/Cr 3 C 2 . The composite could overcome the conflict between the hardness, fracture toughness, and flexural strength.…”
Section: Introductionmentioning
confidence: 99%
“…However, the thermal expansion coefficient of Al 2 O 3 coating and structural materials is quite different, thus the Al 2 O 3 coating is easy to crack and even peel off in a high-temperature environment [15], and the thicker the Al 2 O 3 coating is, the greater the internal stress of the coating, and the easier the coating cracking [16]. To match the coefficient of thermal expansion and improve the bonding strength, the Al transition layer was introduced [17,18]. In a fusion reactor, the nuclear reaction between neutron and 27 Al will produce 24 Na and α particles.…”
Section: Introductionmentioning
confidence: 99%
“…Zaborowska et al [31] studied the evolution of mechanical properties of the irradiated Al 2 O 3 coatings, and the results showed that irradiation-induced softening appeared in the coatings irradiated with 250 keV Au + , irradiationinduced hardening was observed in the coatings irradiated with 150 keV Fe 2+ . The anti-permeation performance of the Al/Al 2 O 3 coating had been investigated in [18]. The change of microstructure and performance of the Al/Al 2 O 3 coating after ion irradiation and the existence of the Al/Al 2 O 3 interface on irradiation resistance is still unknown.…”
Section: Introductionmentioning
confidence: 99%